Usefulness of Bnet, a Simple Linear Metric in Discerning Torsades De Pointes Risks in 28 CiPA Drugs - Han, Sungpil; Han, Seunghoon; Kim, Ki-Suk; Lee, Hyang-Ae; Yim, Dong-Seok (Frontiers in Pharmacology, 2019)
The CiPA (Comprehensive In Vitro Proarrhythmia Assay) project suggested the torsade metric score (TMS) which requires substantial computing resources as a useful biomarker to predict proarrhythmic risk from hERG and a few other ion channel block data. The TMS was useful to predict low TdP risks of drugs blocking Na+ (ranolazine) and Ca2+ (verapamil) channels as well as the hERG channel. However, Mistry asserted that the simple linear metric, Bnet reflecting net blockade of a few influential ion channels has similar predictive power. Here we compared the predictability of Bnet and TMS for the 12 training and 16 validation CiPA drugs which were pre-classified into three categories according to the known TdP risks (low, intermediate and high risk) by CiPA. Bnet at 5xCmax (Bnet5xCmax) was calculated using the ion-channel IC50 and Hill coefficients of CiPA drugs collected from previous reports by the CiPA team and others. The receiver operating characteristic curve area under curve (ROC AUC) values for TMS and Bnet5xCmax as performance metrics in discerning low vs. intermediate/high risk categories for the 28 CiPA drugs were similar. However, Bnet5xCmax was much inferior to TMS at discerning between intermediate- and high-risk drugs. Dynamic Bnet, which used in silico hERG dynamic parameters unlike conventional Bnet, improved the misspecification. Thus, we propose that Bnet5xCmax is used for quick and initial screening of TdP risks of drug candidates and if the ‘intermediate/high’ risk is predicted by Bnet5xCmax, in silico approaches such as dynamic Bnet or TMS may be further considered.